Knowing, Doing, and Becoming Reflective Practitioners: A Narrative Inquiry of STEAM Educators - Sunar, Pushpa Kumari; Pant, Binod Prasad; Dahal, Niroj (Alberta Journal of Educational Research, 2024)
Reflective practice can guide educators toward enhancing their abilities, comprehension, and expertise, reflecting on their experiences to grow personally, professionally, and academically, thereby elevating the overall standard of their work. This paper aims to narrate the perception, practice, challenges, opportunities, and outcomes of reflective practices among STEAM (Science, Technology, Engineering, Arts, Math) educators in Nepal. Using narrative inquiry, we explored the reflective practice experiences of four STEAM educators, (three female and one male). Interview guidelines were used as a data collection tool to generate the participants' narratives. The guiding theoretical referents for this study were Dewey’s theory of experience and Mezirow’s transformative learning theory. The findings of this study show that STEAM educators perceived reflective practice as a tool to reflect on their actions, evaluate them, and learn from their experiences. Participants emphasized that teaching is a dynamic job with many challenges; however, reflective practices helped them realize their weaknesses and refine their efforts to create a better learning environment. It also enabled them to shift from traditional pedagogical practices to progressive ones, where learners were empowered through authentic and meaningful engagement in the learning process. Time management was seen as a significant challenge when practicing reflective practices; sometimes, the ego clash demotivated them to reflect on their actions. Despite challenges, participants also accepted that reflective practices allow them to explore and apply new ideas in their profession and transform their practices. Consequently, the perspectives offered in this paper may prove beneficial for other educators in cultivating reflective practitioners. Keywords: reflective practice, transformation, STEAM educators, narrative inquiry La pratique réflexive peut guider les éducateurs vers l'amélioration de leurs capacités, de leur compréhension et de leur expertise et vers la réflexion sur leurs expériences afin de se développer sur le plan personnel, professionnel et académique, élevant ainsi le niveau général de leur travail. Cet article vise à décrire la perception, la pratique, les défis, les possibilités et les résultats des pratiques réflexives chez les éducateurs STIAM (sciences, technologie, ingénierie, arts et mathématiques) au Népal. En utilisant la méthode de l’enquête narrative, nous avons exploré les expériences de pratique réflexive de quatre éducateurs STIAM (trois femmes et un homme). Des lignes directrices pour les entretiens ont servi d’outils de collecte de données pour générer les récits des participants. Les références théoriques qui ont guidé cette étude sont la théorie de l'expérience de Dewey et la théorie de l'apprentissage transformateur de Mezirow. Les résultats de cette étude montrent que les éducateurs STIAM perçoivent la pratique réflexive comme un outil leur permettant de réfléchir à leurs actions, de les évaluer et de tirer des enseignements de leurs expériences. Les participants ont souligné que l'enseignement est un travail dynamique comportant de nombreux défis ; cependant, les pratiques réflexives les ont aidés à prendre conscience de leurs faiblesses et à affiner leurs efforts pour créer un meilleur environnement d'apprentissage. Elles leur ont également permis de passer de pratiques pédagogiques traditionnelles à des pratiques progressistes, où les apprenants sont responsabilisés par un engagement authentique et significatif dans le processus d'apprentissage. La gestion du temps a été considérée comme un défi important dans la pratique de la réflexion ; parfois, le conflit d'ego les a démotivés à réfléchir à leurs actions. Malgré les difficultés, les participants ont également admis que les pratiques réflexives leur permettaient d'explorer et d'appliquer de nouvelles idées dans leur profession et de transformer leurs pratiques. Par conséquent, les perspectives offertes dans cet article peuvent s'avérer bénéfiques pour d'autres éducateurs en cultivant des praticiens réflexifs. Mots-clés : pratique réflexive, transformation, éducateurs STIAM, enquête narrative